Possibilities for applying blockchain technology – a survey - Mijoska, Mimoza; Ristevski, Blagoj (Informatica, 2021)
The blockchain technology has a potential to be applied in a variety of areas of our daily life. From the original Bitcoin cryptocurrency to the current smart contracts, the blockchain has been applied to many domains. Its numerous applications result in much ongoing research in different practical and scientific areas. This new technology is being seen as a revolutionary solution in finance, decentralization, trust, identity, data ownership and data-driven decisions. This paper presents the novel solutions associated with some of the big data areas that can be empowered by the blockchain technology such as healthcare, decentralized personal data protection, digital property, Internet of Things, digital identity, financial services and infrastructure, e-commerce, educational records, knowledge sharing, insurance, food industry, accounting, auditing and e-voting. Blockchain technology could be used in electronic health records and in the establishment and maintenance of birth registers, deaths, marriages, registration of business activities, but also in the organization of elections. The features of this technology can actually be the redefinition of Internet 3.0 defined as a new type of decentralized infrastructure or network of networks.